Tonoplast- and plasma membrane-localized aquaporin-family transporters in blue hydrangea sepals of aluminum hyperaccumulating plant. - Takashi Negishi (Public Library of Science (PLoS), 2012)
Hydrangea (Hydrangea macrophylla) is tolerant of acidic soils in which toxicity generally arises from the presence of the soluble aluminum (Al) ion. When hydrangea is cultivated in acidic soil, its resulting blue sepal color is caused by the Al complex formation of anthocyanin. The concentration of vacuolar Al in blue sepal cells can reach levels in excess of approximately 15 mM, suggesting the existence of an Al-transport and/or storage system. However, until now, no Al transporter has been identified in Al hyperaccumulating plants, animals or microorganisms. To identify the transporter being responsible for Al hyperaccumulation, we prepared a cDNA library from blue sepals according to the sepal maturation stage, and then selected candidate genes using a microarray analysis and an in silico study. Here, we identified the vacuolar and plasma membrane-localized Al transporters genes vacuolar Al transporter (VALT) and plasma membrane Al transporter 1 (PALT1), respectively, which are both members of the aquaporin family. The localization of each protein was confirmed by the transient co-expression of the genes. Reverse transcription-PCR and immunoblotting results indicated that VALT and PALT1 are highly expressed in sepal tissue. The overexpression of VALT and PALT1 in Arabidopsis thaliana conferred Al-tolerance and Al-sensitivity, respectively.